Preservation of historical schools and heritage tourism in Malaysia / Jamalunlaili Abdullah, Saniah Ahmad Zaki and Suzlyna Abdul Latib - Abdullah, Jamalunlaili; Ahmad Zaki, Saniah; Abdul Latib, Suzlyna (2008)
Malaysia has rich and diverse historic buildings; some are well documented while others are neglected. Unfortunately, those that have been left out and neglected are the historic educational institutions, perhaps because most are still in used as schools. While there are studies that have concentrated only on the architectural design aspect of these few individual schools; few other historic schools had been demolished to make way for development. This paper argues for a comprehensive study of these schools from both the architectural and design perspectives, as well as the socio-politico perspective. From Penang Free School to Malay College Kuala Kangsar to Victoria Institutions in Kuala Lumpur, these schools have significant architectural heritage as well as contributions to local and national development. Thus, the heritage significant of these historic schools can be well appreciated. These historic colonial schools are Malaysian heritage. The paper also proposes educational institutions heritage tourism as part of heritage tourism focusing on these historic schools.